8‐2: Training Multi‐Scale Networks for Compression Artifacts Reduction. Issue 1 (29th May 2019) - Deng, Yufan; Jin, Yufeng; Chen, Yinhung; Zhao, Bin
Abstract : Present a multi‐scale neural network for compression artifacts reduction. The optimized structure and training procedure can lower the difficulty of convergence and speed up training. Experimental results show that our network outperforms other networks, and can remove complex noise in various sizes, generating cleaner images.